PACS A Guide to the Digital Revolution - Dreyer, Keith J.; Hirschorn, David S.; Thrall, James H.; Mehta, Amit (Springer New York : Imprint: Springer, 2006)
In the modern age of digital health care and medical imaging informatics, Picture Archiving and Communications Systems (PACS) have become a fundamental part of the technological infrastructure supporting the practice of radiology. PACS: A Guide to the Digital Revolution, second edition, provides the reader with a comprehensive overview of this blossoming technology. With contributions from leaders in the field of PACS, this user-friendly guide addresses the introductory concepts, computing fundamentals, advanced imaging technologies, and future opportunities. It also offers invaluable concepts and tools that facilitate the financial evaluation of PACS, making it a great resource for those looking to plan for PACS implementation, assess institutional needs, write an RFP, and compare vendors' quotes. The second edition has been revised and updated to keep pace with the rapidly evolving field of picture archiving and communications systems. This new edition includes: An overview of the latest medical imaging standards. A discussion of security issues as they relate to PACS, especially regarding HIPAA. An introduction to current information on PACS workstations, including the impact of new software and hardware on radiologists. An updated explanation of data storage and compression that highlights how advancements are applied. A section on how PACS influences research and education. This text is geared toward radiologists, technologists, administrators, and IT professionals wishing to be a part of the medical imaging revolution.